Efektivitas Pembelajaran PAK Fase E Bermuatan P3 Dengan Metode Think Pair Share Terhadap Prestasi Belajar Di SMA Sint Louis Semarang - Franciska Epilia; Yustinus Joko Wahyu Yuniarto; Hartutik Hartutik (Pusat Riset dan Inovasi Nasional, 2023)
In general, the application of teaching methods and devices in the classroom is still not optimal due to the lack of literature on PAK. Seeing the situation at Sint Louis High School, students are said to be quite heterogeneous so teachers need to prepare appropriate teaching tools. However, the problem is that the development of teaching materials in the new curriculum is still not optimal so that many students experience boredom and less than the maximum attitude of mutual cooperation with friends. The aims of this study were 1) to find out the effect of mutual cooperation on learning achievement using the TPS method assisted by teaching materials containing P3, 2) to find out changes in learning achievement using the TPS method, and 3) to find out the differences in student achievement using the TPS method to achieve mastery. This research is a type of experimental quantitative research, the results of this study show that 1) the average N-Gain score of the experimental class is 72.2 or 72.2%, so the N-Gain is quite effective in increasing student learning achievement, 2) there is a difference in achievement student learning by increasing the mean post-test score which was initially 60.1, after the posttest assessment the average was 88.27, and 3) the results of the simple regression test by testing the variable x (mutual cooperation) on y (learning achievement) showed a positive effect of 86.4%. So, it was concluded that the TPS method assisted by teaching materials based on the Pancasila Student Profile was effective for PAK learning. Suggestions are that teachers and students are able to develop teaching materials and learning media that are creative and of high quality to be given to students